2020
DOI: 10.3390/biom10071079
|View full text |Cite
|
Sign up to set email alerts
|

POSCAbilities: The Application of the Prion Organotypic Slice Culture Assay to Neurodegenerative Disease Research

Abstract: Prion diseases are fatal, transmissible neurodegenerative disorders whose pathogenesis is driven by the misfolding, self-templating and cell-to-cell spread of the prion protein. Other neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis and Huntington’s disease, share some of these prion-like features, with different aggregation-prone proteins. Consequently, researchers have begun to apply prion-specific techniques, like the prion organotypic slice culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 100 publications
(156 reference statements)
0
13
0
Order By: Relevance
“…Organotypic brain slices have been extensively used to study spreading of Aβ and tau in AD or alpha-synuclein in Parkinson´s disease (see [ 37 ].). Organotypic brain slices have been well established in our laboratory for nearly 25 years [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organotypic brain slices have been extensively used to study spreading of Aβ and tau in AD or alpha-synuclein in Parkinson´s disease (see [ 37 ].). Organotypic brain slices have been well established in our laboratory for nearly 25 years [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, compared to in vivo animal models, organotypic cultures require fewer animals, allow real time monitoring and are less expensive. 9 Here, we developed a 3D organotypic spinal cord culture, which well recapitulates the pathogenetic features of SMA and can be used to preliminary screen therapeutic molecules. Indeed, we compared the morphology of SMA and WT MNs, and we observed a significant reduction of cell body area and a remarkable (albeit not significant) axonal length decrease in the SMA samples.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, compared to animal models, organotypic cultures require fewer animals, allow real time monitoring and are less expensive. 9 In this scenario, to easily perform a preliminary screening of promising treatments, 10 we developed a 3D organotypic spinal cord culture (by adapting the most used method, i.e. the 'membrane technique' or interface method 11 ), which well recapitulated the pathogenetic features of SMA: in particular, to assess the neurodegeneration, we evaluated the MN soma size and axonal length, two parameters previously reported as altered in SMA.…”
Section: Introductionmentioning
confidence: 99%
“…Many different brain regions can be cultured, including cerebellum, hippocampus, and cerebral whole brain slices. Organotypic slice culture has been used extensively to study protein folding diseases, including prion disease [ 101 ]. Falsig and Aguzzi developed the Prion Organotypic Slice Culture Assay (POSCA) in which 350 μm-thick cerebellar brain slices from mouse pups are exposed to infectious prions and then cultured for several weeks and accumulate PrP Sc [ 102 ].…”
Section: Organotypic Slice Culturementioning
confidence: 99%
“…Consequently, slice culture, in combination with confocal microscopy, may prove to be a powerful tool for investigating strain tropism. Furthermore, we have recently found that POSCA can be extended to whole brain coronal slices, which significantly increases the scope of brain regions that can be analyzed disease [101] (Figure 1). Organotypic slice cultures provide an open, in vivo-like environment for drug screening.…”
Section: Organotypic Slice Culturementioning
confidence: 99%